Hikers’ pro-environmental behavior in national park: Integrating theory of planned behavior and norm activation theory - Sun, Huazhen; Zhang, Qing; Guo, Weifeng; Lin, Kaimiao (Frontiers in Forests and Global Change, 2022)
The intention of hikers ' pro-environmental behavior directly affects the sustainable development of protected areas, but few studies are conducted from the perspective of theoretical integration. This research explores the intention of hikers' pro-environmental behavior from the perspective of individual hikers, based on theory of planned behavior and norm activation theory. Researchers surveyed 456 hikers hiking in Wuyishan national park, the data analysis method employed was structural equation modeling. The results demonstrate that the TPB model and the NAM model were accept of hikers’ pro-environmental behavior in national park, and for the hiker, their internal demand was considered to precede external stimulus for their behavior. The study sheds light on how to better comprehend and advocate for ERB on national park.